Radiographic comparison of density and height of posterior maxillary bone after open sinus lift surgery with and without PRF - Mohamad Taghi Chitsazi; Ali Hosien Dehghani; Amir Reza Babaloo; Sohrab Amini; Hadi Kokabi (Tabriz University of Medical Sciences, 2018)
Background and aims. Expansion of maxillary sinus towards the alveolar crest due to tooth loss or horizontal‒vertical resorption of the alveolar bone decreases the available bone for the placement of dental implants in the posterior maxilla. The method suggested for placing implants with a standard length is the use of sinus lift surgery with autogenous bone graft or bone substitute materials. The aim of the present research, with split-mouth design, was radiographic comparison of the density and height of the posterior of maxillary bone after open sinus lift procedure with and without PRF. Materials and methods. In this split-mouth clinical trial, 14 patients were evaluated, with complete or partial bilateral edentulism of the upper jaw. In each case, for the sinus lift surgery of the test side, PRF was used, while in the sinus lift surgery of the other side of the same patient no graft materials were used. After six months and before the second surgery, CBCT was used to evaluate bone density and height. Results. All the 41 implants were osseointegrated and were clinically stable. The bone height was 1.42 mm higher in the PRF group than the group without PRF, which was statistically significant. The mean density of the bone formed around the dental implants in the PRF group was 52.85 units higher than that of the group without PRF, which was statistically significant. Conclusion. Using PRF in sinus lift surgery might enhance the quantity and quality of bone formation.